Study on influence of supercritical solvent polarity on diffusivity of polar and non-polar aroma compounds using supercrincal fluid extraction - Azreen Ibrahim (Universiti Malaysia Sabah, 2010)
Supercritical fluid extraction (SFE) is an available and promising technique used to extract volatile compounds from natural products. SFE can be increased by optimizing the process conditions such as pressure, temperature, solvent f10wrate and addition of modifiers. Besides that, the polarity, dipole moment, polarizability, and hydrogen bonding of supercritical solvent used also affect the extraction effectiveness. In this research, SFE is to be used to obtain essential oil from orange peel which contains polar and non-polar aroma compounds. Super critical carbon dioxide is an excellent solvent for non-polar compound like limonene but poor solvent for polar compound like a-terpineol. Common practice in super critical fluid extraction is to change the polarity of super critical carbon dioxide by employing polar modifiers to increase its solvating power towards polar analytes. In this study, effects of adding modifiers with different polarity on extraction of aroma compounds (limonene, linalool and a-terpineol) from Citrus Sinensis L. Osbeck or sweet orange peel were investigated. Super critical extraction was carried out at defined pressure and temperature for duration of 45 minutes. Concentration of aroma compounds extracted was analysed using GC-MS. The optimum conditions for extraction were observed at 318K and 12MPa. The concentrations of Iimonene increased significantly by the addition of methanol and slightly with n-heptane. It was also found that n-heptane is effective on super critical C02 extractions of linalool and a-terpineol.